USE OF THE GENETIC DIVERSITY OF WILD PRUNUS L. SPECIES IN BREEDING OF CLONAL ROOTSTOCKS OF STONE FRUIT CROPS - G. V. Eremin; V. G. Eremin (Труды по прикладной ботанике, генетике и селекции)
Sources and donors of traits important for clonal rootstock breeding have been selected from the genetic diversity of Prunus L. numbering over 5000 genotypes maintained at Krymsk Experimental Breeding Station: adaptability to biotic and abiotic stresses, easy vegetative reproduction ability, dwarfness, etc. As a result of prebreeding, donors combining several breeding traits have been developed.